An SQP trust region method for solving the discrete-time linear quadratic control problem - Mostafa, El-Sayed M.E. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a sequential quadratic programming method combined with a trust region globalization strategy is analyzed and studied for solving a certain nonlinear constrained optimization problem with matrix variables. The optimization problem is derived from the infinite-horizon linear quadratic control problem for discrete-time systems when a complete set of state variables is not available. Moreover, a parametrization approach is introduced that does not require starting a feasible solution to initiate the proposed SQP trust region method. To demonstrate the effectiveness of the method, some numerical results are presented in detail.
Keywords: output feedback control design; sequential quadratic programming; trust region method